(untitled) (TERRA LATINOAMERICANA, 2022)
Infectious pancreatic necrosis virus is one of the most important infectious agents in the salmon and trout industry since it causes high mortality in f irst-fed calves. In Mexico, it is the only viral disease that af fects rainbow trout, therefore, information on the characterization and genetic origin of the viral isolates that circulate in our country have already been described, however, an analysis with the complete genome no, which is why this research work aims to analyze the complete genome of the infectious pancreatic necrosis virus that commonly circulates in the country. Based on the genetic relationships of a prototype of this virus isolated in Mexico in relation to other isolates that circulate worldwide, it was found that the Mexican isolate of infectious pancreatic necrosis virus belongs to genogroup I and originates from the Buhl strain.